PACAP-PAC1 Receptor Activation Is Necessary for the Sympathetic Response to Acute Intermittent Hypoxia - Farnham, Melissa M. J.; Tallapragada, Vikram J.; O’Connor, Edward T.; Nedoboy, Polina E.; Dempsey, Bowen; Mohammed, Suja; Fong, Angelina Y.; Lung, Mandy S. Y.; Derakhshan, Fatemeh; Wilson, Richard J. A.; Pilowsky, Paul M. (Frontiers in Neuroscience, 2019)
Repetitive hypoxia is a key feature of obstructive sleep apnoea (OSA); a condition characterised by intermittent airways obstruction. Patients with OSA present with persistent increases in sympathetic activity and commonly develop hypertension. The objectives of this study were to determine if the persistent increases in sympathetic nerve activity, known to be induced by acute intermittent hypoxia (AIH), are mediated through activation of the pituitary adenylate cyclase activating polypeptide (PACAP) signalling system. Here, we show that the excitatory neuropeptide PACAP, acting in the spinal cord, is important for generating the sympathetic response seen following AIH. Using PACAP receptor knock-out mice, and pharmacological agents in Sprague Dawley rats, we measured blood pressure, heart rate, pH, PaCO2, and splanchnic sympathetic nerve activity, under anaesthesia, to demonstrate that the sympathetic response to AIH is mediated via the PAC1 receptor, in a cAMP-dependent manner. We also report that both intermittent microinjection of glutamate into the rostroventrolateral medulla (RVLM) and intermittent infusion of a sub-threshold dose of PACAP into the subarachnoid space can mimic the sympathetic response to AIH. All the sympathetic responses are independent of blood pressure, pH or PaCO2 changes. Our results show that in AIH, PACAP signalling in the spinal cord helps drive persistent increases in sympathetic nerve activity. This mechanism may be a precursor to the development of hypertension in conditions of chronic intermittent hypoxia, such as OSA.